2009
DOI: 10.1104/pp.108.132134
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of PEBP Genes in Barley Reveal the Diversification of Their Roles in Flowering    

Abstract: Five barley (Hordeum vulgare) PEBP (for phosphatidylethanolamine-binding protein) genes were analyzed to clarify their functional roles in flowering using transgenic, expression, and quantitative trait locus analyses. Introduction of HvTFL1 and HvMFT1 into rice (Oryza sativa) plants did not result in any changes in flowering, suggesting that these two genes have functions distinct from flowering. Overexpression of HvFT1, HvFT2, and HvFT3 in rice resulted in early heading, indicating that these FT-like genes ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
165
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(185 citation statements)
references
References 39 publications
12
165
1
3
Order By: Relevance
“…1a). Subgroup IA contains AcFT1 and AcFT2 as well as the monocot FTs implicated in regulating flowering in rice 33 (Hd3a and RFT1), barley 34,35 (HvFT1 and HvFT2) and orchid 36 (CgFT; Fig. 1a, proteins marked with asterisk).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). Subgroup IA contains AcFT1 and AcFT2 as well as the monocot FTs implicated in regulating flowering in rice 33 (Hd3a and RFT1), barley 34,35 (HvFT1 and HvFT2) and orchid 36 (CgFT; Fig. 1a, proteins marked with asterisk).…”
Section: Resultsmentioning
confidence: 99%
“…1a, proteins marked with asterisk). AcFT4 is positioned within subgroup IIA that also contains the FT-like proteins associated with the flowering of maize 32 (ZmZCN8) and barley 34,35 (HvFT3). AcFT3, AcFT5 and AcFT6 proteins are located in FT-like subgroup IB and a role has not been established for any of the proteins within this subgroup.…”
Section: Resultsmentioning
confidence: 99%
“…vegetative versus floral) and floral integrator genes are also highly conserved, particularly FT, which has been shown to act as a mobile signal acting in the manner of 'florigen' in rice (Tamaki et al 2007), tomato (Lifschitz et al 2006) and Arabidopsis (Corbesier et al 2007), with similar roles suggested in several other plant species including grasses, sunflowers, poplar and morning glory (Turck et al 2008;Kikuchi et al 2009;Blackman et al 2010). Related genes that, like FT, carry a phosphatidyl ethanolamine-binding protein domain appear to be involved in the determination of phenological traits and/or onset of reproduction over evolutionary time dating all the way to bryophytes (Hedman et al 2009) and spruce (Gyllenstrand et al 2007).…”
Section: Seasonal Cues Regulating Plant Phenologymentioning
confidence: 99%
“…TSF has a small effect on flowering additive with FT, and the TSF protein, like FT, can act as a mobile inducer of flowering when expressed in the phloem (Jang et al, 2009). In contrast with the similarity in regulation of FT and TSF, multiple FT-like genes in other species show marked differences in regulation (Faure et al, 2007;Kikuchi et al, 2009;Blackman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%